Solve the question and enter the value of x below.
2x 9 = 21
x = _____
17 answers
x = 6
Solve the question and enter the value of x below.
13x + 7 = 215
x = ____
13x + 7 = 215
x = ____
To solve the equation, we need to isolate the variable x by moving the constant term 7 to the other side of the equation. Here's the step-by-step solution:
13x + 7 = 215
Subtract 7 from both sides:
13x = 215 - 7
13x = 208
Now, divide both sides of the equation by 13 to solve for x:
x = 208 / 13
x ≈ 16
Thus, the value of x is approximately 16.
13x + 7 = 215
Subtract 7 from both sides:
13x = 215 - 7
13x = 208
Now, divide both sides of the equation by 13 to solve for x:
x = 208 / 13
x ≈ 16
Thus, the value of x is approximately 16.
Solve the question and enter the value of x below.
-3x - 9 = -27
x = ____
-3x - 9 = -27
x = ____
To solve the equation, we need to isolate the variable x by moving the constant term -9 to the other side of the equation. Here's the step-by-step solution:
-3x - 9 = -27
Add 9 to both sides:
-3x = -27 + 9
-3x = -18
Now, divide both sides of the equation by -3 to solve for x:
x = -18 / -3
x = 6
Thus, the value of x is 6.
-3x - 9 = -27
Add 9 to both sides:
-3x = -27 + 9
-3x = -18
Now, divide both sides of the equation by -3 to solve for x:
x = -18 / -3
x = 6
Thus, the value of x is 6.
Solve the question and enter the value of x below.
-4x - 13 = 51
x = _____
-4x - 13 = 51
x = _____
To solve the equation, we need to isolate the variable x by moving the constant term -13 to the other side of the equation. Here's the step-by-step solution:
-4x - 13 = 51
Add 13 to both sides:
-4x = 51 + 13
-4x = 64
Now, divide both sides of the equation by -4 to solve for x:
x = 64 / -4
x = -16
Thus, the value of x is -16.
-4x - 13 = 51
Add 13 to both sides:
-4x = 51 + 13
-4x = 64
Now, divide both sides of the equation by -4 to solve for x:
x = 64 / -4
x = -16
Thus, the value of x is -16.
Solve the question and enter the value of x below.
7x + (-2) = -44
x = _____
7x + (-2) = -44
x = _____
To solve the equation for x, we need to isolate x by moving -2 to the other side of the equation. Here's the step-by-step solution:
7x + (-2) = -44
Add 2 to both sides:
7x = -44 + 2
7x = -42
Next, divide both sides by 7 to solve for x:
x = -42 / 7
x = -6
Thus, the value of x is -6.
7x + (-2) = -44
Add 2 to both sides:
7x = -44 + 2
7x = -42
Next, divide both sides by 7 to solve for x:
x = -42 / 7
x = -6
Thus, the value of x is -6.
Solve the question and enter the value of y below.
6y + 3 = 45
y = _____
6y + 3 = 45
y = _____
To solve for y, we need to isolate the variable y by moving the constant term 3 to the other side of the equation. Here's the step-by-step solution:
6y + 3 = 45
Subtract 3 from both sides:
6y = 45 - 3
6y = 42
Now, divide both sides of the equation by 6 to solve for y:
y = 42 / 6
y = 7
Thus, the value of y is 7.
6y + 3 = 45
Subtract 3 from both sides:
6y = 45 - 3
6y = 42
Now, divide both sides of the equation by 6 to solve for y:
y = 42 / 6
y = 7
Thus, the value of y is 7.
Solve the equation and enter the value of x below.
6x + 7 = 43
x = ____
6x + 7 = 43
x = ____
To solve the equation, we need to isolate the variable x by moving the constant term 7 to the other side of the equation. Here's the step-by-step solution:
6x + 7 = 43
Subtract 7 from both sides:
6x = 43 - 7
6x = 36
Now, divide both sides of the equation by 6 to solve for x:
x = 36 / 6
x = 6
Thus, the value of x is 6.
6x + 7 = 43
Subtract 7 from both sides:
6x = 43 - 7
6x = 36
Now, divide both sides of the equation by 6 to solve for x:
x = 36 / 6
x = 6
Thus, the value of x is 6.
What is the next operation required to isolate the variable?
4x + 6 = 18
÷ 3
÷ 6
- 18
- 6
4x + 6 = 18
÷ 3
÷ 6
- 18
- 6
To isolate the variable x in the equation 4x + 6 = 18, the next operation required would be subtracting 6 from both sides of the equation.
Solve the equation and enter the value of x below.
-9x - 3 = 60
x = _____
-9x - 3 = 60
x = _____
To solve the equation, we need to isolate the variable x by moving the constant term -3 to the other side of the equation. Here's the step-by-step solution:
-9x - 3 = 60
Add 3 to both sides:
-9x = 60 + 3
-9x = 63
Now, divide both sides of the equation by -9 to solve for x:
x = 63 / -9
x = -7
Thus, the value of x is -7.
-9x - 3 = 60
Add 3 to both sides:
-9x = 60 + 3
-9x = 63
Now, divide both sides of the equation by -9 to solve for x:
x = 63 / -9
x = -7
Thus, the value of x is -7.